2014
DOI: 10.1111/jcmm.12214
|View full text |Cite
|
Sign up to set email alerts
|

Selenium induces a multi‐targeted cell death process in addition to ROS formation

Abstract: Selenium compounds inhibit neoplastic growth. Redox active selenium compounds are evolving as promising chemotherapeutic agents through tumour selectivity and multi-target response, which are of great benefit in preventing development of drug resistance. Generation of reactive oxygen species is implicated in selenium-mediated cytotoxic effects on cancer cells. Recent findings indicate that activation of diverse intracellular signalling leading to cell death depends on the chemical form of selenium applied and/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
56
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(60 citation statements)
references
References 33 publications
3
56
0
1
Order By: Relevance
“…Furthermore, GS‐Se‐SG at 8 μ M concentration has been shown to selectively induce apoptosis in squamous carcinoma cells compared to normal mucosa cells by induction of Fas‐ligand (Fas‐L) expression, and activation of the stress pathway by increased expression of JNK and p38 . This is also in line with recent findings in our laboratory, where GS‐Se‐SG (5 μ M ) was able to glutathionylate cell surface proteins and induce apoptosis more readily, compared to selenite (5 μ M ) . CysSeSeCys treatment at various concentrations (5–40 μ M ) and time has been reported to induce a S‐phase arrest and apoptosis via ERK and Akt in MCF‐7 cells .…”
Section: Selenium and Programmed Cell Deathsupporting
confidence: 91%
“…Furthermore, GS‐Se‐SG at 8 μ M concentration has been shown to selectively induce apoptosis in squamous carcinoma cells compared to normal mucosa cells by induction of Fas‐ligand (Fas‐L) expression, and activation of the stress pathway by increased expression of JNK and p38 . This is also in line with recent findings in our laboratory, where GS‐Se‐SG (5 μ M ) was able to glutathionylate cell surface proteins and induce apoptosis more readily, compared to selenite (5 μ M ) . CysSeSeCys treatment at various concentrations (5–40 μ M ) and time has been reported to induce a S‐phase arrest and apoptosis via ERK and Akt in MCF‐7 cells .…”
Section: Selenium and Programmed Cell Deathsupporting
confidence: 91%
“…In human cell lines, selenite, but not Sec, was also shown to result in accumulation of mitochondrial superoxide (Wallenberg et al, 2010) and impair mitochondrial structure (Wallenberg et al, 2014). Additionally, treating human cells with Sec resulted in an increase of Se in protein, and this was associated with an unfolded protein selenite selenite selenocysteine selenoprotein Selenium assimil ation p athway transl ation misfolded p rotein reactive oxygen species…”
Section: Discussionmentioning
confidence: 98%
“…Overall, these results implied that SeCys formation plays a central role in SeMet-induced growth inhibition, which suggests that SeMet mode of action should be similar to that of SeCys. In this context, it is interesting to note that, in a recent study by Kupsco and Schlenk (146), exposure of fish (Japanese medaka) embryos to SeMet combined with hypersalinity induced a 100-fold increase in transcripts of BiP, the major ER chaperone (146), suggesting an accumulation of misfolded proteins in the ER reminiscent of the SeCystine-induced ER stress observed by Wallenberg et al (120) in HeLa cells.…”
Section: Selenomethionine Toxicitymentioning
confidence: 89%
“…The same authors showed that SeCystine triggered endoplasmic reticulum (ER) stress, the unfolded protein response, an increase in protein ubiquitination and extensive cytoplasmic vacuolarization in HeLa cells, in the absence of DNA damage (120). In higher plants also, evidence was recently provided that SeCys treatment impairs protein homeostasis without elevation of superoxide levels (121,122).…”
Section: Selenocyst(e)ine Toxicitymentioning
confidence: 98%